The meaning of centrality and margin in Lisbon’s Rossio: spatializing urban processes before and after the 1755 earthquake - Malet Calvo, D. (2015)
Praça do Rossio has been the most emblematic space in central Lisbon both before and after the 1755 earthquake that destroyed much of the city. Up until the thirteenth century Rossio was a barren area outside the walls of the medieval city and was used as a common space where people held ceremonies for 500 years. The Rossio also connected inland rural area with the city within the walls, acting as a bridge between those two worlds. For this reason Rossio has always been a space for all kind of vendors, outsiders, beggars and social rejects, while also a route into the city for agrarian culture, rituals and people. Despite the attempts by the city’s masters and the Crown to seize the space for the construction of their institutions, it was not until the 1755 earthquake that this finally happened. The reconstruction of Lisbon under the gaze of the enlightened rationalist Marquis of Pombal represented the beginning of a new era for the city: giving birth to the modern bourgeois city, in which the historical organization of space was reshaped, the Rossio’s traditional functions displaced and the meaning and contents of the hegemonic city representations and imaginaries such as fado music and the annual People’s Saints (Santos Populares) celebrations renewed. In this article, the centrality of Rossio is reviewed, with a stress on the displacement of some of its attributes to the districts after the earthquake by the romantic heritage processes of meaning. However, the Rossio maintained some of its traditional functions, with the daily presence there of African migrants as an example